Chemistry, asked by Maan9809, 1 year ago

Balance the following equation using oxidation number method
As₂S₃ + HNO₃ + H₂O → H₃AsO₄ + H₂SO₄ + NO

Answers

Answered by abhi178
12
As₂S₃ + HNO₃ + H₂O → H₃AsO₄ + H₂SO₄ + NO

step 1 :- 20H₂O + As₂S₃ ⇔ 2H₃AsO₄ + 3H₂SO₄ + 28H⁺ + 28e⁻ ----(1)
step 2 :- + 3H⁺ + HNO₃ ⇔ NO + 2H₂O - 3e⁻ ----(2)

multiply 3 with equation (1) and 28 with equation (2),
3[20H₂O + As₂S₃ ⇔ 2H₃AsO₄ + 3H₂SO₄ + 28H⁺ + 28e⁻ ]
60H₂O + 3As₂S₃ ⇔ 6H₃AsO₄ + 9H₂SO₄ + 84H⁺ + 84e⁻

28[3H⁺ + HNO₃ ⇔ NO + 2H₂O - 3e⁻]
84H⁺ + 28HNO₃ ⇔ 28NO + 56H₂O - 84e⁻

Now, add both equations
60H₂O + 3As₂S₃ ⇔ 6H₃AsO₄ + 9H₂SO₄ + 84H⁺ + 84e⁻
84H⁺ + 28HNO₃ ⇔ 28NO + 56H₂O - 84e⁻
________________________________________
4H₂O + 3As₂S₃ + 28HNO₃ ⇒6H₃AsO₄ + 9H₂SO₄ + 28NO [balanced]
Answered by ramritinbandaru1234
0

Answer:

As₂S₃ + HNO₃ + H₂O → H₃AsO₄ + H₂SO₄ + NO

step 1 :- 20H₂O + As₂S₃ ⇔ 2H₃AsO₄ + 3H₂SO₄ + 28H⁺ + 28e⁻ ----(1)

step 2 :- + 3H⁺ + HNO₃ ⇔ NO + 2H₂O - 3e⁻ ----(2)

multiply 3 with equation (1) and 28 with equation (2),

3[20H₂O + As₂S₃ ⇔ 2H₃AsO₄ + 3H₂SO₄ + 28H⁺ + 28e⁻ ]

60H₂O + 3As₂S₃ ⇔ 6H₃AsO₄ + 9H₂SO₄ + 84H⁺ + 84e⁻

28[3H⁺ + HNO₃ ⇔ NO + 2H₂O - 3e⁻]

84H⁺ + 28HNO₃ ⇔ 28NO + 56H₂O - 84e⁻

Now, add both equations

60H₂O + 3As₂S₃ ⇔ 6H₃AsO₄ + 9H₂SO₄ + 84H⁺ + 84e⁻

84H⁺ + 28HNO₃ ⇔ 28NO + 56H₂O - 84e⁻

________________________________________

4H₂O + 3As₂S₃ + 28HNO₃ ⇒6H₃AsO₄ + 9H₂SO₄ + 28NO [balanced]

Explanation:

Similar questions